Efforts to Overcome the Crime of Murder in the Family Reviewed from a Criminological Perspective - Zai, Selfiani; Pakpahan, Kartina; Sihotang, Feby Putri Shoshanny; Tarigan, Michelle Yonesta (JURNAL MERCATORIA, 2025)
This article aims to analyze efforts to prevent the crime of murder within the family environment from a criminological perspective and to examine criminal responsibility and punishment imposed on perpetrators. The problem is focused on the occurrence of murder cases within the family environment in North Sumatra Province and the factors contributing to these crimes, based on seven reported cases from online media news between 2021 and 2024. In order to approach this problem, criminological theory and criminal law theory are used as the theoretical references to understand the causes of crime and the application of criminal liability. The data is collected through a normative-empirical legal research method, including literature studies, analysis of statutory regulations such as the Criminal Code (KUHP), Law Number 23 of 2004 concerning the Elimination of Domestic Violence, Law Number 1 of 2023, and the examination of relevant online media reports, and analyzed qualitatively. This study concludes that efforts to prevent the crime of murder in the family can be carried out through penal and non-penal approaches. Penal efforts emphasize the enforcement of criminal sanctions, while non-penal efforts focus on preventive measures through education, strengthening family resilience, the role of religious institutions, police involvement, and psychological assistance. The causative factors include emotional instability, parenting patterns, economic pressure, social environment, and weak law enforcement. Effective prevention requires cross-sectoral collaboration to create a just, preventive, and sustainable crime prevention system, while punishment serves both retributive and rehabilitative purposes.